FACTORS AFFECTING MEDICAL STUDENTS’ STRESS DURING COVID-19 PANDEMIC: A CROSS-SECTIONAL STUDY - Limanda, Claudia Felicia; Purnawati, Susy; Adiputra, Luh Made Indah Sri Handari; Tirtayasa, Ketut (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Since the emergence of COVID-19 in 2019, Indonesia’s COVID-19 Task Force has implemented distance or online learning in educational sectors, especially in Java and Bali. In its implementation, a certain number of medical students developed a tendency to prefer online learning compared to face-to-face learning without completely understanding its risks. Other factors such as financial barriers, social isolation, limitation of physical activity, change of diet, and anxiety-prone tendencies in COVID-19 pandemic, not much further research has been carried out. This study aims to determine whether medical students’ stress can be aggravated by several factors, namely online learning, financial barriers, social isolation, limitation of physical activity, change of diet, and anxiety-prone tendencies in order to obtain information whether online learning can be applied, even when the pandemic is over.Methods: Research design used a quantitative approach. Data collection was performed through online questionnaires distributed to 238 medical students selected using simplified random sampling. Data was analysed descriptively and inferentially. Inferential analysis used T-Test and ANOVA Test.Results: Online learning, financial barriers, social isolation, limitation of physical activity, change of diet, and anxiety-prone tendencies independently and cumulatively elevate medical students’ stress. Cumulatively, independent factors mentioned above have 85% effect in aggravating of medical students’ stress.Conclusion: Online learning application has to be reconsidered due to additional stress implicated to medical students. In addition, financial barriers, social isolation, limitation of physical activity, change of diet, and anxiety-prone tendencies are important factors in aggravating medical students’ stress.